Type 1 Diabetes Is Associated With Enterovirus Infection in Gut Mucosa - Oikarinen, Maarit; Tauriainen, Sisko; Oikarinen, Sami; Honkanen, Teemu; Collin, Pekka; Rantala, Immo; Mäki, Markku; Kaukinen, Katri; Hyöty, Heikki (Diabetes (New York, N.Y.), 2012)
Enterovirus infections have been linked to type 1 diabetes in several studies. Enteroviruses also have tropism to pancreatic islets and can cause β-cell damage in experimental models. Viral persistence has been suspected to be an important pathogenetic factor. This study evaluates whether gut mucosa is a reservoir for enterovirus persistence in type 1 diabetic patients. Small-bowel mucosal biopsy samples from 39 type 1 diabetic patients, 41 control subjects, and 40 celiac disease patients were analyzed for the presence of enterovirus using in situ hybridization (ISH), RT-PCR, and immunohistochemistry. The presence of virus was compared with inflammatory markers such as infiltrating T cells, HLA-DR expression, and transglutaminase 2-targeted IgA deposits. Enterovirus RNA was found in diabetic patients more frequently than in control subjects and was associated with a clear inflammation response in the gut mucosa. Viral RNA was often detected in the absence of viral protein, suggesting defective replication of the virus. Patients remained virus positive in follow-up samples taken after 12 months' observation. The results suggest that a large proportion of type 1 diabetic patients have prolonged/persistent enterovirus infection associated with an inflammation process in gut mucosa. This finding opens new opportunities for studying the viral etiology of type 1 diabetes.